Alterations of Bone Density, Microstructure, and Strength of the Distal Radius in Male Patients With Rheumatoid Arthritis: A Case‐Control Study With HR‐pQCT. (September 2014) - Zhu, Tracy Y; Griffith, James F; Qin, Ling; Hung, Vivian W; Fong, Tsz‐Ning; Au, Sze‐Ki; Li, Martin; Lam, Yvonne Yi‐On; Wong, Chun‐Kwok; Kwok, Anthony W; Leung, Ping‐Chung; Li, Edmund K; et al.
ABSTRACT In this cross‐sectional study, we investigated volumetric bone mineral density (vBMD), bone microstructure, and biomechanical competence of the distal radius in male patients with rheumatoid arthritis (RA). The study cohort comprised 50 male RA patients of average age of 61.1 years and 50 age‐matched healthy males. Areal BMD (aBMD) of the hip, lumbar spine, and distal radius was measured by dual‐energy X‐ray absorptiometry. High‐resolution peripheral quantitative computed tomography (HR‐pQCT) of the distal radius provided measures of cortical and trabecular vBMD, microstructure, and biomechanical indices. aBMD of the hip but not the lumbar spine or ultradistal radius was significantly lower in RA patients than controls after adjustment for body weight. Total, cortical, and trabecular vBMD at the distal radius were, on average, –3.9% to –23.2% significantly lower in RA patients, and these differences were not affected by adjustment for body weight, testosterone level, or aBMD at the ultradistal radius. Trabecular microstructure indices were, on average, –8.1% (trabecular number) to 28.7% (trabecular network inhomogeneity) significantly inferior, whereas cortical pore volume and cortical porosity index were, on average, 80.3% and 63.9%, respectively, significantly higher in RA patients. RA patients also had significantly lower whole‐bone stiffness, modulus, and failure load, with lower and more unevenly distributed cortical and trabecular stress. Density and microstructure indices significantly correlated with disease activity, severity, and levels of pro‐inflammatory cytokines (interleukin [IL] 12p70, tumor necrosis factor, IL‐6 and IL‐1β). Ten RA patients had focal periosteal bone apposition most prominent at the ulnovolar aspect of the distal radius. These patients had shorter disease duration and significantly higher cortical porosity. In conclusion, HR‐pQCT reveals significant alterations of bone density, microstructure, and strength of the distal radius in male RA patients and provides new insight into the microstructural basis of bone fragility accompanying chronic inflammation. © 2014 American Society for Bone and Mineral Research.